Medical Tourism and Inclusive Growth in Karnataka - Madappa, D. (International Research Journal of Management, IT & Social Sciences, 2015)
Medical tourism has emerged as a critical component of tourism in India. Medical tourism, a subset of health tourism, is an emerging segment of tourism industry and there are only a few serious studies conducted on the topic. With the growing importance of medical tourism and the thrust given by central and state governments to promote tourism, the paper explores the potential role of Ayurveda in medical tourism sector. A survey of practitioners, manufacturers, researchers, representatives of various associations in Ayurveda sector was carried out and the findings of the survey, which have policy implications, have been used to explore the possibilities of promoting Ayurveda sector in the medical tourism with the participation of local government institutions and community in order to achieve inclusive growth. The dominance of small and medium enterprises, individual researchers and practitioners, and labor intensive operations in Ayurveda based medical tourism and its impact on inclusive growth is highlighted. The paper also aims to formulate an action plan to address the critical issues of Ayurveda sector to enable it to play a central role in medical tourism.Â